EFFECT OF THE HYDROGEN PEROXIDE AND SALICYLIC ACID ON INDUCTION THE SOD GENE EXPRESSION OF DATE PALM (Phoenix dactylifera L.) AS DEFENSE FACTOR AGAINST SALINITY STRESS - Aljassani, I. F.; Alqaisi, M. R. M.; Al-Ahbabi, A. J. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This experiment was conducted in order to determine the effect of spraying acid salicylic (SA) at concentrations of 250, 500 mg L-1 and hydrogen peroxide H2O2 at 3% and 6% compared with water as a control treatment on three cultivars of date palm tree (Barhi, Hilali and Majhoul), which are propagated via tissue culture under salt stress conditions, to estimate the gene expression of Superoxide dismutase (SOD), The SA 250 and 500 mg L-1 for Folding values achieved the highest gene expression for the cultivar Barhi and Hilali, which reached 2.549121, 3.363586, 5.098243, and 4.924578, respectively, While the highest gene expression of this enzyme for the Majhoul when treated with 6% hydrogen peroxide, which was recorded at 2.828427.